The Concept of The Adverb of Time and Place in Arabic Grammar : (Sebuah studi analitis dalam sebuah buku penjelasan yang sangat singkat di Mukhtashar Al-Jarumiyyah, halaman 22) - M AbduL Ghofur; Imam Wahyudi (Al-Kafaah : Journal of Arabic Language and Linguistics Education (ALLE), 2023)
This study aims to analyze matters relating to the adverb of time and adverb of place, because in the Arabic text it is very important to study it so that we know the information of time and place, and not mistakenly use it. The existence of this research is expected to be able to provide an overview of dhorf and its use in Arabic text and provide benefits to writers and readers. This research uses descriptive method with a qualitative approach. The research subject is the book Syarh Muhtasor Jiddan Ala Matni Jurumiah page 22. The results of this study are that the dhorf of time and eating really needs to be studied because it has a serious impact on understanding Arabic texts, especially on the use of the drorf. Which will have an impact on the meaning and grammatically.